Potencjał i procesy innowacyjne - Łunarski, Jerzy; Stadnicka, Dorota (Innovational Potential and Processes, 2006)
In the paper the authors tried to identify the innovational potential, which should be rightly managed to create proper environment, favorable to generate innovations. To make a good innovational management system the innovational processes should be first identified and described. The paper shows how to identify processes, how to describe them and how to manage them. The goal of this paper is to provoke the discussion about the possibility of establishing the best innovational management system, which consists of environment management and innovations management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 307-314